Cognitive Behavior Therapy untuk Mengatasi Masalah Psikologis Pasien Kanker - Marthalila, Eko Putra; Novieastari, Enie; Hargiana, Giur; Gayatri, Dewi (FORIKES, 2025)
Cancer is one of the leading causes of death worldwide. Patients with cancer face many challenges and problems, one of which is psychological problems including depression, stress, anxiety, and sleep disorders. The purpose of this study was to determine the effectiveness of cognitive behavioral therapy to overcome psychological problems in cancer patients. The method used in this study was a systematic review through several databases, namely PoQuest, ScienceDirect, Sage Journals, and SpringerLink. The procedure used was Preferred Reporting Items for Systematic reviews and Meta-Analyses. Literature searches were carried out with systematic and strict steps, including critical appraisal using Critical Appraisal Skills Programme, so that 10 research articles were obtained with a randomized controlled trial design that met the criteria. The results of the study showed that based on a review of the selected articles, cognitive behavioral therapy, both in standard and combination formats, is effective in helping cancer patients with psychological problems including depression, stress, anxiety, and sleep disorders. A tailored approach, a combination with other methods such as hypnosis and the use of technology shows good potential for future psychological interventions. The conclusion of the study showed that cognitive behavioral therapy is an effective option to overcome psychological problems in cancer patients.Keywords: cancer patients; psychological problems; cognitive behavioral therapy ABSTRAK Kanker merupakan salah satu penyebab utama kematian di seluruh dunia. Pasien dengan penyakit kanker menghadapi banyak tantangan dan permasalahan, salah satunya masalah psikologis meliputi depresi, stress, kecemasan, dan gangguan tidur. Tujuan dari studi ini adalah untuk mengetahui efektivitas cognitive behavioral therapy untuk mengatasi masalah psikologis pasien kanker. Metode yang digunakan dalam studi ini adalah systematic review melalui beberapa database yaitu PoQuest, ScienceDirect, Sage Journals, dan SpringerLink. Prosedur yang digunakan adalah Preferred Reporting Items for Systematic reviews and Meta-Analyses. Penelusuran literatur dilakukan dengan langkah yang sistematis dan ketat, termasuk critical appraisal dengan menggunakan Critical Appraisal Skills Programme, sehingga didapatkan 10 artikel penelitian dengan rancangan randomized controlled trial yang memenuhi kriteria. Hasil studi menunjukkan bahwa berdasarkan tinjauan terhadap artikel-artikel terpilih, cognitive behavioral therapy, baik dalam format standar maupun kombinasi, efektif untuk membantu penerita kanker dengan masalah psikologis meliputi depresi, stress, kecemasan, dan gangguan tidur. Pendekatan yang disesuaikan, kombinasi dengan metode lain seperti hipnosis dan penggunaan teknologi menunjukkan potensi baik untuk intervensi psikologis di masa depan. Kesimpulan studi menunjukkan bahwa cognitive behavioral therapy merupakan pilihan yang efektif untuk mengatasi masalah psikologis pasien kanker.Kata kunci: pasien kanker; masalah psikologis; cognitive behavioral therapy